Yoga by the numbers: the sacred and symbolic in yoga philosophy and practice - Rosen, Richard (Shambhala, 2022)
"A fascinating explanation of the significant, often symbolic role that numbers play in yoga philosophy-by beloved yoga teacher and writer Richard Rosen. Numbers play a meaningful role in the philosophy of many spiritual traditions-and yoga is no exception. For example, the number one is the quintessential yoga number, representing "unity" and "wholeness"; number two sometimes stands for co-operative effort, and other times for conflict; and number four is the number of completeness or stability, as it "stands" on "four legs." There are twelve different names for the mantra OM, each one revealing a different aspect of this root sound. With his distinctive blend of knowledge and humor, Richard Rosen unpacks the fascinating significance that numbers hold in the philosophy and practice of yoga. Stories and practices woven throughout-like the Eka Danta simple meditation exercise, which concentrates on "one pointedness" and is associated with the one tusk of Ganesh-offer readers a hands-on way to explore the importance of numbers in their own practice. Yoga by the Numbers will enlighten and entertain the yogi in your life"--